HUBUNGAN TERPAAN IKLAN TVC BUKALAPAK DAN TINGKAT PENDAPATAN DENGAN MINAT BERTRA DI BUKALAPAK - Prio Wicaksono; Sri Widowati Herieningsih (Interaksi Online, 2019)
Advertisement is a promotional instrument that can easily communicate with consumers about the convenience and superiority of a product or service. Bukalapak becomes the online retail store with the highest budget for TVC advertisement, which spends 813,78 billion rupiah. Bukalapak allocated the biggest budget for TVC advertisement but still sits on the fourth place based on Top Brand Award survey. Information gathering is one of the characteristics of transaction interest. With an increase in income, there should be an equal increase in buying interest. According to BPS Jateng, in 2018 the average income of the residents was Rp. 36,78 million/year. The average income of Central Java residents has increased from Rp. 34,22 million/year in 2017. The objective of the study is to understand the correlation between TVC advertising exposure of Bukalapak and income level with the transaction interest in Bukalapak. The theory used is Advertising Exposure Theory and Social Category Theory. This is a quantitative study with explanatory research methodology. The writer uses non-probability sampling technique with a sample of 65 people in the 17-34 age range who live in Semarang and are exposed to Bukalapak’s TVC advertisement and receive monthly income. Based on the hypothesis testing using Kendall’s Tau correlation analysis, it is found that there is a positive connection between Bukalapak’s TVC with transaction interest in Bukalapak with a significance number of 0,000 and correlation coefficient of 0.845. On another variable between income levels and transaction interest in Bukalapak, there is a positive connection with a significance number of 0,000 and correlation coefficient of 0,687. The conclusion of the study reveals that there is a positive connecction between Bukalapak’s TVC and income level with buying interest in Bukalapak. With the said result, it is recommended for Bukalapak to conduct research to make the advertisement strategy more effective in front of the audiences.